EDUCATION OF MAINTAIN DENTAL AND ORAL HEALTH AT TAMBAKREJO STATE ELEMENTARY SCHOOL, SIDOARJO - Irianingtyas, Riza; Rahmania, Nima Eka Nur; Kuncoro, Achmad; Maryiantari, Ellyza Setya (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
The counseling activity on maintaining dental and oral health given to class V and VI students at SDN Tambakrejo Surabaya is a form of community service in the form of presenting material and simulations which are expected to maintain health and prevent dental and oral disease in children. The extension activities will be held on December 9, 2023 at SDN Tambakrejo Waru Sidoarjo. Before carrying out extension activities, there is an activity preparation process for approximately four weeks before implementing the activity, starting from determining the type of activity to submitting permits to the relevant parties. As a form of evaluation, this activity was attended by 42 elementry school students of classes V and VI, the participants took part in the activity very enthusiastically and the counseling guidance activity ran smoothly.